Immunological role of neuronal receptor vanilloid receptor 1 expressed on dendritic cells - Basu, Sreyashi (National Academy of Sciences, 2005)
Capsaicin (CP), the pungent component of chili pepper, acts on sensory neurons to convey the sensation of pain. The CP receptor, vanilloid receptor 1 (VR1), has been shown to be highly expressed by nociceptive neurons in dorsal root and trigeminal ganglia. We demonstrate here that the dendritic cell (DC), a key cell type of the vertebrate immune system, expresses VR1. Engagement of VR1 on immature DCs such as by treatment with CP leads to maturation of DCs as measured by up-regulation of antigen-presenting and costimulatory molecules. This effect is present in DCs of VR1(+/+) but not VR1(–/–) mice. In VR1(+/+) mice, this effect is inhibited by the VR1 antagonist capsazepine. Further, intradermal administration of CP leads to migration of DCs to the draining lymph nodes in VR1(+/+) but not VR1(–/–) mice. These data demonstrate a powerful influence of a neuroactive ligand on a central aspect of immune function and a commonality of mechanistic pathways between neural and immune functions.